(untitled) (Research, Society and Development, 2022)
The search for improvements in the quality of endodontic preparations allowed the evolution of instruments that were manual for mechanized instruments. This study sought to compare the performance of reciprocating files after the fourth use, observing the modeling potential, cleaning efficiency in simulated root canals, taking into account procedural errors. Seventy-two acrylic blocks were used, divided into two groups: Waveone Gold and W-file. o The groups were subdivided into 4 according to the number of uses. Black Nankin paint was used to fill these blocks, which were covered with aluminum foil, so that there was no influence on the operator’s handling. Irrigation was performed with distilled water to eliminate debris. Pre- and post-instrumentation images were performed to compare before and after instrumentation. For statistical information, tests such as Shapiro-wilk, for independent samples and Mann Whitney were used. Among the experimental and limited conditions of the present study, after the fourth use, it was possible to observe that there were some significant differences and that the W-file instrument proved to be more conservative and with greater centralization when compared to the WaveOne Gold.